Social determinants in research on economic freedom of university graduates: a bibliometric and content analysis - Cortés , Eleaquim E. Torres; Carmona, Eduardo Alejandro; Esparza, Reina Margarita Vega (Iberoamerican Journal of Science Measurement and Communication, 2022)
Objective. Find the social determinants that influence or contribute to achieving economic freedom in students or university graduates. Design/Methodology/Approach. The study presents a quantitative methodology, with a descriptive exploratory scope, through a bibliometric analysis using the SciMAT software on 748 scientific publications collected from Scopus on the topic: "Economic Freedom", all with a holistic approach. In this period, from 2005 to 2020. Said analysis identifies the main authors, organizations, countries, sources, research areas and development of this field of research. Results/Discussion. A conceptual evolution map is obtained for each thematic area of the social determinants that influence or contribute to achieving economic freedom in students or university graduates in the period 2005-2020. Three areas remain as determinants: social factors, emotional behavior and educational status. The scientific community has focused its attention on the university graduate as a person who has individual aspirations and perspectives; however, there are also variables such as parental education, educational status, socioeconomic and psychological factors, etc. Conclusions. The concept of economic freedom has evolved in recent years; researchers on the subject have reached conclusions or consensus, describing the elements or general conditions that constitute it. This paper delimits the scientific discussion on "economic freedom" in three thematic areas: social factors, emotional behavior, and educational status, which affect students or university graduates.